1994
DOI: 10.1063/1.111372
|View full text |Cite
|
Sign up to set email alerts
|

Very large magnetoresistance in perovskite-like La-Ca-Mn-O thin films

Abstract: Colossal magnetoresistance with more than a thousandfold change in resistivity (ΔR/RH=127 000% at 77 K, H=6 T) has been obtained in epitaxially grown La-Ca-Mn-O thin films. This magnetoresistance value is about three orders of magnitude higher than is typically seen in the giant-magnetoresistance-type metallic, superlattice films. The temperature of peak magnetoresistance is located in the region of metallic resistivity behavior. As the magnetoresistance peak occurs not at the temperature of magnetic transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
142
2
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(154 citation statements)
references
References 16 publications
6
142
2
4
Order By: Relevance
“…Thin films of La-Ca-Mn-O, [18][19][20][21] La-Ba-Mn-O, 22 La-(Ca,Pb)-Mn-O, 23 La-Ce-Mn-O, 24 and La-Sr-Mn-O 25 exhibit magnetoresistance in the range of 5%-150%, which is comparable to that obtained in giant magnetoresistance (GMR) metal multilayers. Jin et al and McCormack et al reported 26,27 a "colossal" magnetoresistance of more than 100 000% for epitaxial La-Ca-Mn-O films on LaAlO 3 . The origin of these enormous magnetoresistance values is unknown, although they evidently are related to the magnetic state of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films of La-Ca-Mn-O, [18][19][20][21] La-Ba-Mn-O, 22 La-(Ca,Pb)-Mn-O, 23 La-Ce-Mn-O, 24 and La-Sr-Mn-O 25 exhibit magnetoresistance in the range of 5%-150%, which is comparable to that obtained in giant magnetoresistance (GMR) metal multilayers. Jin et al and McCormack et al reported 26,27 a "colossal" magnetoresistance of more than 100 000% for epitaxial La-Ca-Mn-O films on LaAlO 3 . The origin of these enormous magnetoresistance values is unknown, although they evidently are related to the magnetic state of the system.…”
Section: Introductionmentioning
confidence: 99%
“…10 With small substitutions of the perovskite crystal structure, the conductivity can be tuned from insulating toward metallic behavior, for example, for colossal magnetoresistance 11 or transparent conductors. 12 All these perovskite materials and their properties have opened access to considerable research activities and multiple applications.…”
Section: Introductionmentioning
confidence: 99%
“…and B stands for divalent alkaline-earth elements, such as Ba, Sr, etc. Materials refinements have revealed that very large magnetoresistances, of over three orders of magnitude change in resistance, can be observed in such compounds prepared through special heat-treatment (Jin et al, 1994a;Jin et al, 1994b;McCormack et al, 1994). These materials have since been refered to as colossal magnetoresistance materials, or CMR materials.…”
Section: Introductionmentioning
confidence: 99%